Cost-accuracy and patient experience assessment of blood pressure monitoring methods to diagnose hypertension: A comparative effectiveness study - González-de Paz, Luis; Kostov, Belchin; Freixa, Xavier; Herranz, Carmen; Lagarda, Elena; Ortega, María; Pérez, Elisa; Porcar, Silvia; Sánchez, Eva; Serrato, Montserrat; Vidiella, Ingrid; Sisó-Almirall, Antoni (Frontiers in Medicine, 2022)
Objectives: Studies of the diagnosis of hypertension have emphasized long-term cost-effectiveness analysis, but the patient experience and costs of blood pressure monitoring methods at the diagnosis stage remain unclear. We studied four diagnostic methods: a new 1h-automated office blood pressure (BP) monitoring, office BP measurement, home BP monitoring, and awake-ambulatory BP monitoring. Methods: We carried out a comparative effectiveness study of four methods of diagnosing hypertension in 500 participants with a clinical suspicion of hypertension from three primary healthcare centers in Barcelona city (Spain). We evaluated the time required and the intrinsic and extrinsic costs of the four methods. The cost-accuracy ratio was calculated and differences between methods were assessed using ANOVA and Tukey's honestly significant difference post hoc test. Patient experience data were transformed using Rasch analysis and re-scaled from 0 to 10. Results: Office BP measurement was the most expensive method (€156.82, 95% CI:156.18 to 157.46) and 1h-automated BP measurement the cheapest (€85.91, 95% CI: 85.59 to 86.23). 1h-automated BP measurement had the best cost-accuracy ratio (€ 1.19) and office BP measurement the worst (€ 2.34). Home BP monitoring (8.01, 95% CI: 7.70 to 8.22), and 1h-automated BP measurement (7.99, 95% CI:7.80 to 8.18) had the greatest patient approval: 66.94% of participants would recommend 1h-automated BP measurement as the first or second option. Conclusions: The relationship between the cost-accuracy ratio and the patient experience suggests physicians could use the new 1h-automated BP measurement as the first option and awake-ambulatory BP monitoring in complicated cases and cease diagnosing hypertension using office BP measurement